MANAJEMEN KEMITRAAN UNTUK MENINGKATKAN KOMPETENSI GURU: PENDEKATAN BERBASIS KOLABORASI DENGAN INDUSTRI - Taufiqurrohman, Taufiqurrohman; Hidayati, Dian; Maryani, Ika (STKIP Pesisir Selatan, 2024)
This research aims to develop a partnership-based training model to improve the competence of automotive vocational teachers in line with the Industrial Revolution 4.0 and Society 5.0. By involving the automotive industry, this model seeks to align industry needs with teacher competencies, so as to better prepare SMK graduates to enter the workforce. This research uses a research and development (R&D) method with two stages: development and validation. Education experts, SMK teachers, and industry practitioners were involved through interviews, FGDs, and questionnaires. The study involved 72 vocational automotive teachers in Central and West Java. The implementation of the model was piloted in three national automotive industries, with evaluation based on observation and feedback from trainees. The training model consists of six stages: (1) Communication and Information, (2) Facilitation, (3) Mentoring, (4) Monitoring, (5) Process Evaluation, and (6) Results Evaluation. The model was well received by the teachers, increasing their motivation, knowledge and skills, and aligning their competencies with industry standards. This research introduces a partnership-based model that directly involves industry, fosters sustainable collaboration and increases the relevance of teacher training to labor market needs, improving the quality of vocational education.